Investigation of air-water two-phase flow characteristics in a 25.4 mm diameter circular pipe. (August 2021) - Wang, Dewei; Shi, Shanbin; Fu, Yucheng; Song, Kyle; Sun, Xiaodong; Tentner, Adrian; Liu, Yang
Abstract: High-quality two-phase flow data are essential for further developing various two-phase flow models and validating two-phase flow codes. The work presented in this paper aims to perform detailed measurements of air-water two-phase flow in a 25.4 mm inner diameter pipe using several techniques developed recently. The gas-phase information is obtained by an integrated method synergizing conductivity probe, high-speed imaging system, and X-ray densitometry system while the Particle Image Velocimetry and Planar Laser-Induced Fluorescence (PIV-PLIF) technique are utilized to measure liquid-phase velocity and turbulence characteristics. Selected conditions in the bubbly, slug, and churn-turbulent flow regimes with the gas and liquid superficial velocities ranging from 0.05 to 4.99 m/s and from 0.10 to 3.88 m/s, respectively, are investigated in this work. The two-phase flow interfacial structures are visualized by both high-speed optical and X-ray images. In fully developed bubbly flows, "wall-peak" void profiles are observed, which is due to the transverse lift force effect. The gas-phase velocities share similar profiles as the liquid-phase velocity but have slightly higher magnitudes due to the buoyancy force effect. In this work, flow development in different flow regimes is investigated as well. As bubbly flows develop along the axial direction, the void profiles may change, and the discrepancy between gas-phase and liquid phase velocities will diminish in the process.